Community Service: Training on Creating Dry Herbarium As A Learning Media For Senior High School Students : Pengabdian kepada Masyarakat: Pelatihan Membuat Herbarium Kering Sebagai Media Pembelajaran Untuk Siswa Sekolah Menengah Atas Negeri 11 Kota Jambi - Asra*, Revis; Adriadi, Ade; Suprayogi, Dawam; Ul Maritsa, Hasna; Wahyuni, Fitra (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service program aimed to enhance the competencies of senior high school teachers and students in creating a simple herbarium as an environmentally based biology learning medium. The program employed tutorials and group mentoring, receiving positive feedback from all participants. During the training, five plant species were successfully identified and converted into herbarium specimens, thereby improving practical knowledge and skills. The findings indicate that the use of herbarium effectively deepens students’ understanding of biological concepts through interactive activities both in the classroom and in the laboratory. Additionally, the program fostered the utilization of local biodiversity within the school environment, raising awareness of ecosystem conservation. Overall, the development of a simple herbarium contributed significantly to achieving biology learning objectives in senior high schools and can continue to serve as a sustainable educational resource.